Technological Advancements in Monoclonal Antibodies - José F. Santos-Neto; Fabricia O. Oliveira; Katharine V. S. Hodel; Larissa M. S. Fonseca; Roberto Badaró; Bruna A. S. Machado (The Scientific World Journal)
Biopharmaceuticals are innovative solutions that have revolutionized the treatment of important chronic diseases and malignancies. The approval of biosimilar products has become a complex and balanced process, and there are versions of drugs with established biosimilarity that can offer a more accessible treatment option to patients. The objective of this work was to identify the advancement of these technologies by means of patent and article analysis based on technological and scientific prospection. In patent document recovery, Derwent Innovation Index (DWPI) and PatentInspiration databases were used. The research was based on the search of the selected terms in the title, summary, and claims of the documents through a search strategy containing IPC code and keywords. In articles recovery, the Web of Science tool was used in the search of scientific publications dated from the last 5 years. The search resulted in a total of 2295 individual patent documents and 467 families using DWPI database, 769 individual patents and 205 families using PatentInspiration, and 2602 articles using Web of Science database. Additionally, this work describes the number of organizations that contribute to this area, where they are, how much development they have undergone, and the inventors/authors involved. Based on the number of publications registered, there is an important prominence for scientific research in mAbs. In terms of innovation, it is expected that several therapeutic drugs are already under regulatory review, which will allow drugs to be approved over the next few years and will thus generate a continuous flow of new products based on immunotherapies, mAbs, and biosimilar drugs. These drugs have become essential weapons for the treatment of significant diseases, and the increasing trend in the number of related scientific and technological publications contributes to making these therapies available to the greatest number of people.